3D reactive printing of polyaniline hybrid hydrogel microlattices with large stretchability and high fatigue resistance for wearable pressure sensors. (22nd March 2022) - Yue, Meichen; Wang, Yufeng; Guo, Hele; Zhang, Chao; Liu, Tianxi
Abstract: Conducting polymer hydrogels face difficulties in the combination of high elasticity, large sensitivity and wide response range for flexible pressure sensing. Herein, an intrinsically stretchable polyaniline hybrid hydrogel (PHH) is prepared through a reactive shaping method including two steps. First, a high-viscosity precursor solution containing poly(acrylic acid) (PAA), poly(ethylene oxide) (PEO) and aniline monomers is submerged into an acid solution containing initiators for the polymerization of aniline, and gelation is quickly formed due to the formation of dense hydrogen bonds between the PAA and PEO chains. Second, the initiators in the acid solution facilitate subsequent in-situ polymerization of aniline confined in the PAA/PEO framework into a 3D polyaniline (PANI) network. Benefiting from the formation of reversible hydrogen bonds and electrostatic interactions between the PAA/PEO and PANI networks, the resultant PHH exhibits large stretchability and high fatigue resistance. The reactive shaping method facilitates a 3D reactive printing of PHH into pre-designed microlattice structures with high elasticity and electron/ion dual-conducting pathways, which is promising as a stretchable conductor for capacitive pressure sensors. The sensors therefore display high sensitivity (7.10 kPa −1 ) in a wide detecting range and are capable of detecting complex human motions for wearable sensing applications. Graphical abstract: Image 1